2022
DOI: 10.1016/j.cmi.2021.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Re: ‘ESCMID COVID-19 living guidelines: drug treatment and clinical management’ by Bartoletti et al

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Concern about use of remdesivir has been previously raised following observation coming from real world data [ 36 , 37 ]. However, in the PINETREE trial patients receiving remdesivir did not experience a higher rate of severe adverse events and other adverse events when compared with controls ( Table 4 ).…”
Section: Pico 19: What Is the Effect Of Remdesivir Treatment (I) On M...mentioning
confidence: 99%
“…Concern about use of remdesivir has been previously raised following observation coming from real world data [ 36 , 37 ]. However, in the PINETREE trial patients receiving remdesivir did not experience a higher rate of severe adverse events and other adverse events when compared with controls ( Table 4 ).…”
Section: Pico 19: What Is the Effect Of Remdesivir Treatment (I) On M...mentioning
confidence: 99%
“…Most patients with self-reported long COVID were not hospitalized due to their SARS-CoV-2 infection and only had mild symptoms of the infection itself. New studies indicate that people at higher risk are women, people aged 35 to 69, socioeconomically deprived people, people working in social care, people belonging to ethnic minorities, and people with other activity-limiting illnesses [4,19,20]. Studies also found that long COVID impacts children of all ages [4,9,14,21].…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms affect many different organs and physiological pathways, can be interrelated and all need to be studied more profoundly. The symptoms can be clustered into systems: they can affect neurological and cognitive, cardiovascular, gastrointestinal, dermatological and respiratory/pulmonary systems [4,5,[14][15][16]19]. Impacts can also be on the reproductive system with effects, for example, on menstruation, yet sex-speci c pathophysiology has to be studied in more detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have read with great interest the recent comment by dr. Dauby considering cardiovascular side-effects of remdesivir [ 1 ] that might question its role in the treatment of severe COVID-19 patients [ 2 ]. At the moment bradycardia is considered to be most frequent cardiovascular side-effect of remdesivir and occurs due to undisclosed mechanism.…”
mentioning
confidence: 99%